Internal impingement instability of the shoulder - van der Woude, H.-J.; Willems, J. (Medicine and Science in Tennis, 2007)
In shoulder pathology, impingement can be classified as external impingement (primary or secondary) and internal impingement. Primary external impingement is secondary to contact between the rotator cuff and coracoacromial arch. Secondary external impingement reflects rotator cuff tendinosis and tears as a result of accentuated glenohumeral (micro)instability. This is typically seen in sports that require overhead or throwing motions. As a result of weakened static stabilisers, more load is placed on dynamic stabilisers including the rotator cuff muscles, resulting in fatigue of muscles, superior migration of humeral head and impingement of the rotator cuff.